Development of Heterogeneous Catalysts for Formation of Biodiesel - Vishal (My University, 2014)
In present thesis, heterogeneous catalysts for the transesterification of triglycerides have been developed. Four types of catalysts were prepared viz.; (i) KOH impregnated MgO (ii) potassium impregnated mixed oxides of La and Mg (iii) potassium impregnated SiO2 (iv) KNO3 and MgO modified mesoporous SBA-15. These catalysts were characterized by powder XRD, TEM, SEM-EDX, TGA/DTA, FT-IR, Hammett indicators and soluble basicity measurements. In addition to this work, commercially available sodium aluminate has also been evaluated for the transesterification. Potassium hydroxide (5-20 wt.%) impregnated MgO catalysts were prepared by wet-impregnation followed by drying and calcination. Powder XRD and DTA studies support the formation of heterogeneised potassium species over MgO during calcination at 550oC. TEM studies supported that size of these particles are in the range 20-45 nm. Prepared catalysts were used for the transesterification of mutton fat and optimized reaction parameters were the 4 wt.% of MgO-KOH-20 (MgO impregnated with 20 wt.% of KOH), 1:22 molar ratio of fat to methanol, 65oC reaction temperature and 20 min of reaction duration. Potassium impregnated mixed oxides of La and Mg in 1: 1 to 1: 5 atomic ratios were prepared by co-precipitation method. TEM studies of these oxides supported the formation of polygonal, square and hexagonal shaped particles. The catalyst prepared by using 1: 3 atomic ratio of La to Mg was found to have stronger basic sites and better activity towards the transesterification reaction of used cotton seed oil. Under optimized reaction conditions of 1: 54 molar ratio of oil to methanol and 5 wt.% of the catalyst (prepared with La to Mg atomic ratio of 1:3 at pH 10) at 65oC reaction temperature, 96% FAME yield was obtained in 20 min. Concentration of potassium ions leached out from catalyst into biodiesel was found within permissible limit of ASTM iv Potassium impregnated SiO2 having 1:1 to 1:6 atomic ratios of Si to K were prepared by sol gel method and evaluated as heterogeneous catalysts for the transesterification of jatropha and karanja oil with methanol. TEM studies of the catalyst having Si and K in 1:6 atomic ratio reveals that catalyst has uniform impregnation of 1-5 nm sized potassium nanoparticles over 15-40 nm sized spherical silica nanoparticles. Same catalyst was found to be efficient for the transesterification of jatropha and karanja oil in 0.3 h and 0.75 h respectively at 65oC. Mesoporous SBA-15 wrapped with MgO was prepared by one pot synthesis. It was further coated with the third layer of KNO3 (10-30 wt.%) via grinding in the presence of water followed calcination at 600oC under nitrogen atmosphere for 4 h. Coating of MgO prevents the destruction of SBA-15 from potassium as MgO acts as a obstruction and prevents the direct contact between potassium and SBA-15. The BET surface area and pore volume of SBA-15 modified with 20 wt.% of MgO and 25 wt.% of KNO3 was found to be 183 m2/g and 0.39 cm3/g respectively. These values are less than that observed for SBA-15 wrapped with MgO to indicate that potassium species have been incorporated inside the mesoporous sieves. The material showed super basic nature and was used as a catalyst for the transesterification of used cotton seed oil with methanol to produced biodiesel with > 98% conversion. Sodium aluminate and its calcined forms have been evaluated as basic catalysts for the transesterification of waste mutton fat with methanol. The decrease in catalytic activity has been observed with calcined sodium aluminate. Fat and methanol in 1:29 molar ratio with 1.5 wt.% of sodium aluminate under reflux resulted in 97 % conversion to biodiesel in 1h 20 min. The catalyst was found to effective even in the presence of 1 wt.% of moisture.
PHD, SCBC
Keywords: Biodiesel; Heterogeneous catalyst